2017
DOI: 10.12691/ijdsr-5-3-2
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Chicken Egg Shell Powder Solution (CESP) on Artificially Induced Dental Erosion: An in Vitro Atomic Force Microscope Study

Abstract: Aim: The aim of this in vitro study was to evaluate the effect of chicken egg shell powder solution (CESP) on the dental erosion produced by Coca Cola drink in permanent teeth. Material and methods: Thirty extracted human incisors were collected for this study purpose. After extraction all the specimens were cleaned and sectioned longitudinally resulting in 60 samples from a total of 30 tooth samples. All samples were randomly assigned to the following three groups. Group 1: Untreated group, Group 2: Demineral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 21 publications
2
12
0
Order By: Relevance
“…Surface roughness and micro-hardness results revealed that, topical treatment with CESP slurry significantly reduced the mean surface roughness and enhanced the micro-hardness of the de-mineralized group II tooth specimens that indicated the process of re-mineralization. The present finding is supported by those of Feroz and Moeen (25) and Feroz et al (26) who recorded enhancement on the hardness and decrease on the surface roughness following the use of CESP. Thus, it was enhancing the in-vitro re-mineralization of eroded enamel.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Surface roughness and micro-hardness results revealed that, topical treatment with CESP slurry significantly reduced the mean surface roughness and enhanced the micro-hardness of the de-mineralized group II tooth specimens that indicated the process of re-mineralization. The present finding is supported by those of Feroz and Moeen (25) and Feroz et al (26) who recorded enhancement on the hardness and decrease on the surface roughness following the use of CESP. Thus, it was enhancing the in-vitro re-mineralization of eroded enamel.…”
Section: Discussionsupporting
confidence: 91%
“…Numerous studies tried to evaluate the effects of various re-mineralizing agents on early enamel caries stage, however shortage of data still present about the application of CESP and its efficiency on the treatment of eroded surface of enamel caused by pediatric medications (25,26) .…”
Section: Introductionmentioning
confidence: 99%
“…Haghgoo et al (2016) (26) showed that ESP significantly increased the microhardness of artificial enamel carious lesions. Feroz et al (2017) (27) showed that ESP significantly reduced surface roughness of erosive enamel lesions. Mony et al (2015) (28) found that ESP solution can remineralize the enamel, and highlighted the need of studying another suitable vehicle for ESP.…”
Section: Llena Et Al (2015)mentioning
confidence: 99%
“…In addition to the treatment of WSLs, Feroz et al (2017) (27) evaluated the effect of ESP on enamel erosive lesions invitro found that ESP reduced the surface roughness and was effective against erosive enamel lesions. Similarly, Yaberi and Haghgoo (2018) (30) performed an in-situ study to compare the effects of NHA and ESP on the microhardness of third molars enamel following soft drink exposure, and found that both that NHA and ESP have the capability to remineralize erosive lesions.…”
Section: Llena Et Al (2015)mentioning
confidence: 99%
“…In this study atomic analysis by EDX(energy dispersive X-ray spectrometry) was done which shows highest Ca concentration of 98%. According to SandleenFeroz (2017) 11 the protective effects of chicken egg shell powder solution on enamel was compared with samples treated with demineralizing solution and the results showed a statistically significant difference (0.158±0.012) with a p value of 0.00 indicating the effectiveness of remineralizing effect of CESP on enamel surfaces. The statistical results were similar with our results.…”
Section: Resultsmentioning
confidence: 99%